Procedure For Use of Groundwater for Irrigation of Agricultural Crops (Texas Journal of Engineering and Technology, 2023)
Systematic use of surface and underground water along with surface water is one of the important resources for increasing the production of agricultural products, obtaining a high yield and dramatically improving the melioration of irrigated lands